Domestic violence: a Rodger's evolutionist conceptual analysis - Victoria Grassi Bonamigo; Deborah Ribeiro Carvalho; Marcia Regina Cubas
ABSTRACT Objective: to analyze the concept of domestic violence based on its use in health sciences, humanities, and exact sciences according to Rodgers' evolutionary model. Methods: this is a concept analysis based on Rodgers' evolutionary conceptual model. Ninety-six articles were included in Portuguese, English, Spanish, and French, which had a definition of domestic violence, having identified the antecedents, attributes and consequences and produced a model case. Results: twenty-two attributes, ten antecedents and eight consequences were identified. Final considerations: from antecedents, attributes and consequences, it was possible to identify the connection between domestic violence and gender issues, especially patriarchal, being seen in a normalized way by society and causing consequences to the victims' physical and psychological health.